APPLICATION OF COMMUNICATION SERVICES OF LIBRARY SERVICES IN IMPROVING COMMUNITY READING LOVE CULTURE - Har Yati (Jurnal Neo Societal, 2023)
Regional public libraries have a very important role to foster the development of reading and increase information literacy in the community. The government has always viewed the library development as sporadic. And there are still many who do not meet the National Library Standards. Based on Law Number 43 of 2007 concerning the National Library Standards Article 32, one of them reads "Library staff is obliged to provide excellent service to the visitors. . In this study, there are three problem formulations, namely: 1). How is the Application of Communication Services in the Library and Archives Office of Karimun Regency. 2). Factors that become obstacles in carrying out services to improve the culture of fond of reading in the community, and 3). How does the culture of reading society in Karimun Regency. This type of research used in this research is descriptive qualitative. Where the data obtained in the process and analyzed with relevant theory, so as to obtain a picture of the object of research and then can be drawn a conclusion about the problem under study. In this study researchers used two data sources, namely 1). Primary Data Sources that are directly collected by researchers in the field are obtained from the main sources. . 2). Secondary Data Sources are data obtained to supplement as a source of primary data sources obtained from literature and other sources. The instrument used in data collection was in the form of interviews, in which the researcher prepared in advance a systematic list of question points. And a closed questionnaire where the answer choices have been determined. Then make observations in the field. Based on this study the target population is employees who play a direct role in service to the Library and Archives Service and visitors. Sampling is determined by the researchers themselves. The sample is done purposively by selecting subjects based on the specific set by the researcher. Researchers determined that the sample in this study amounted to 7 (seven) respondents consisting of the Head of Office, Head of Library Development and Culture of Reading Fondness, Head of Management, Preservation of Library Materials and Library Services. Head of Karimun Regency Library and Archive Services Section and staff and visitors. The theory that supports research is Laswell's theory of the 5 (five) elements of communication, also called the five dimensions of communication. The results of this study that the application of communication services conducted by the Library and Archives Office of Karimun Regency can be said to be good because the average obtained from the whole statement is 83% although there are several inhibiting factors in its implementation.